ANALISIS TERHADAP PERKARA KETERLAMBATAN PELAPORAN AKUISISI (PERKARA NOMOR 02/KPPU-M/2018) - Budiyanto, Didik; Abbas, Ahmad Sudirman; Iswandi, Irvan (Journal of Islamic Studies, 2023)
There are currently laws against monopolies and business competition in more than 80 nations worldwide and more than 20 other countries are trying to draft the same laws. In the current era of globalization, business competition in the trade market is getting tighter. Companies are required to always develop strategies and create new innovations to maintain their existence. One of the crucial legal tools in a market economy is competition law. The government aims to safeguard healthy competition between market participants through commercial competition law. This kind of study is done in libraries using a normative legal framework that draws on societal norms as well as legal standards found in laws, rules, and court rulings. The aims of this research are to find out the optimization of Law Number 5 of 1999 concerning the Commission for the Supervision of Business Competition (KPPU) for resolving monopoly problems and unfair business competition, and to find out the obligation to notify share acquisition by Savings and Loans Services Cooperatives. The results of the study concluded that KPPU has the authority over corporate actions carried out by Kospin Jasa in the form of acquisition of PT. ATU. Based on the principle of accountability based on the element of error, Kospin Jasa has legal responsibility for its actions. Mistakes made by Kospin Jasa are errors in the form of negligence.